Clinical evaluation of balance in hemiparetic adults: a systematic review - Carla Bambirra; Maria Cecília de Betsan Rodrigues; Christina Danielli Coelho de Morais Faria; Fátima Rodrigues de Paula
Introduction Hemiparesis is a common post-stroke impairment often associated with balance deficits. Standardized instruments for balance assessment may be useful in identifying individuals at risk of falling and evaluating intervention outcomes. Objectives To identify instruments with adequate psychometric properties and clinical application to assess balance in hemiparetic cases within the scope of physiotherapy and to verify tools most frequently used in studies that evaluated the effects of therapeutic interventions in order to improve the balance of hemiparetic patients. Methods A search was conducted in the Medline, Lilacs, PEDro, and Web of Science databases by two independent researchers, who selected and analyzed studies that evaluated the reliability and validity of balance assessment instruments and intervention results. Results and discussion The Berg Balance Scale was the most frequently used instrument in the intervention studies. Nine single-task tests (timed up and go, functional reach test, step test, four-square step test, side step test, supported standing balance, standing arm raise, static tandem standing, and weight shifting) and six multiple-task tests (Berg balance scale, Brunel balance assessment, Fugl-Meyer Assessment/balance section, mini balance evaluation systems test, and postural assessment scale for stroke patients) demonstrated adequate psychometric properties and clinical applications to assess balance in hemiparetic individuals. Conclusions The Berg Balance Scale had the most widely studied psychometric properties and was the most frequently used scale in the intervention studies. Further studies are required to validate and adapt other instruments for the Brazilian population.